PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS PBL TOPIK HIMPUNAN KELAS VII SMP/MTS - KURNIA SRI HAMDAYANI (Departemen Matematika, 2021)
Research conducted is aimed at developing the proposed learning design and based learning problem worksheet based learning on topic vii junior/MTS class set. In the process of doing so, using a plomp model consisting of the first three stages of investment, the development stage, or the development of the prototype and the assessment stage. In part of the initial investment, the analysis of needs, the curriculum analysis, the concept and analysis of learners. Thus acquired the characteristics of the developed learning device. So at the stage of development the prototype is done with the design of the prototype learning device of the learning implement plan and an embedded resource worksheet for complex materials. So the outcome of the prototype would have to go through an formative evaluation of its own evaluation and an expert evaluation in order to obtain a valid one. While the latter part of the assessment is based on the assessment, this part of the assessment aims to determine the practical criteria of the i.t. prototype used the research was carried out at the time of the outbreak of covid-19, resulting in several phases of the study that could not be properly implemented. As a result of developing the learning plan and based learning problem based learning worksheet based on a categorized set topic valid and practical based on the plomp prototype stage. Keywords — design research, learning tools, Problem Based Learning, Sets